Inspirasi Origami dalam Desain Logo - Waradya, Vera; Bimo, Arjo (Bina Nusantara University, 2013)
From time to time design trends have adapted in certain styles. One is the art of origami. It inspires many graphic designers in 2009, mainly design logo and typeface. Origami is the traditional Japanese folk art of paper folding, turning a piece of paper into a beautiful shape that is a work of art in itself. And with its simplicity and geometric shapes, origami logo design is used by companies who want to represent modern, delicacy, attention to detail, precision, and elegance.